Tingkat Pengetahuan Remaja Tentang Penyiapan Kehidupan Berkeluarga Bagi Remaja (PKBR) Pada PIK-R Dan Non PIK-R (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2024)
Background: Adolescents are the future of a nation and ensuring their high capacity is crucial for country development. However, the phenomenon of early marriage is common and is one of the major adolescents’ concernsin Indonesia. Youth Information and Counselling Centre (PIK-R) is a container-managed preparation of family lifeprogram activitiesof, by and for youth to provide information and counseling about PKBR (Preparation of FamilyLife For Adolescents) and other support activities. From the results of a preliminary study in the Purwomartanivillage still many marriages at a young age and the high divorce rate that occurred in the region.Objective: To determine differences in the level of adolescents knowledge about preparation of family life for adolescents at PIK-R and no PIK-R.Methode: This research uses study comparative design with cross sectional approach models. Respondents inthis research is adolescents aged 18-21 years of the total 78 respondents. There is 39 from PIK-R and 39 from noPIK-R. The instrument used in this research is the questionnaire. Bivariate analysis using Man Whitney test.Results: The level of adolescents knowledge about PKBR at PIK-R in good categories were 21 (55.26%), while atno PIK-R in good categories as much as 9 (23.68%). Man Whitney analysis with p-value 0.000 (